Market Concentration Index and Performance: Evidence from Indonesian Banking Industry - Jumono, Sapto; Abdurrahman, Abdurrahman; Fath Mala, Chajar Matari (International Journal of Economics and Financial Issues, 2017)
The aim of this research is to evaluate the loan market, deposit market, and performance based on basic earning power (BEP) and return on equity (ROE). This research also investigates the relationship between markets and performance. Structure-Conduct-Performance (SCP) theory is used as the grand theory. This research uses 97 samples from the publication of financial report during 2011-2014. The inferential analysis is conducted by GMM Arellano-Bond. The research result showed that concentration market index has a significant influence of BEP and ROE, meanwhile market share does not have a significant influence on BEP and ROE. According to SCP theory, this result shows that Indonesian banking industry is in the collusive condition and is not efficient yet. Keywords : concentration index, market share, loan, deposits, BEP and ROE JEL Classifications: C23; G21; L11